A web to evaluate the schools (Journal of Parents and Teachers, 2023)
This article exposes a project called “IDEA” that tries to improve the evaluation of the different schools. To evaluate, it considers a lot of factors to get more completed results.
Keywords: IDEA; project; evaulation